2020
DOI: 10.1002/dev.22066
|View full text |Cite
|
Sign up to set email alerts
|

The longitudinal negative impact of early stressful events on emotional and physical well‐being: The buffering role of cardiac vagal development

Abstract: Early stressful events negatively affect emotional and physical well‐being. Cardiac vagal tone (CVT), which is associated with better emotional and physical well‐being, usually gradually increase in early childhood. Nonetheless, children's CVT developmental trajectories are greatly variable, such that CVT can increase or decrease across the years. The present study examines the longitudinal effects of early stressful events and the role of 4 years CVT developmental trajectory on children's emotional and physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…Previous literature has shown how classroom climate is positively linked with students’ engagement (Wang et al, 2020), yet here we bring evidence that the increase in the ability to self‐regulate can help students to be engaged in classroom activities despite the perception of an emotionally negative classroom climate. Hence, congruently to what has been found in relation to the increase in basal CVT (Patron et al, 2021), a positive change in CVT response to stress seems to be an important protective factor. Future studies should better investigate how a more active adjustment can be beneficial within the classroom, however, even if these data are preliminary, they indicate that next to promoting a positive classroom climate, it can be useful to work on teaching children how to improve their self‐regulatory skills.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Previous literature has shown how classroom climate is positively linked with students’ engagement (Wang et al, 2020), yet here we bring evidence that the increase in the ability to self‐regulate can help students to be engaged in classroom activities despite the perception of an emotionally negative classroom climate. Hence, congruently to what has been found in relation to the increase in basal CVT (Patron et al, 2021), a positive change in CVT response to stress seems to be an important protective factor. Future studies should better investigate how a more active adjustment can be beneficial within the classroom, however, even if these data are preliminary, they indicate that next to promoting a positive classroom climate, it can be useful to work on teaching children how to improve their self‐regulatory skills.…”
Section: Discussionsupporting
confidence: 85%
“…Hence, interventions fostering children's self‐regulation should be promoted in order to support the positive developmental growth of the system's physiological ability to adapt to everyday challenges. Strengthening the ability to restore homeostasis after experiencing a source of stress is functional for student engagement not only in the short (Mastromatteo et al, 2021) but also in the long term (Patron et al, 2021). In addition, we here support the well‐known importance of promoting a positive classroom climate to foster engagement (Berkowitz et al, 2017; Thapa et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other empirical evidence may provide insight into how childhood maltreatment and heart rate variability can interact to predict grief symptoms over time. For example, Patron et al (2020) recently found that high heart rate variability acted as a protective factor among children who experienced a high number of early stressful events. Specifically, among children who experienced a higher number of early stressful events, a positive cardiac vagal tone development trajectory was associated with better physical well-being.…”
Section: Discussionmentioning
confidence: 99%
“…from 2:30 p.m. to 5:30 p.m.) in order to minimize the circadian effects on the physiological measures (e.g. O’Súilleabháin et al, 2017; Patron et al, 2020; Tyra et al, 2020). Upon arrival, participants were given several minutes to acclimate to the laboratory environment.…”
Section: Methodsmentioning
confidence: 99%